The Staphylococcus aureus Protein-Coding Gene gdpS Modulates sarS Expression via mRNA-mRNA Interaction - Chen, Chuan (Infect Immun, 2015)
Staphylococcus aureus is an important Gram-positive pathogen responsible for numerous diseases ranging from localized skin infections to life-threatening systemic infections. The virulence of S. aureus is essentially determined by a wide spectrum of factors, including cell wall-associated proteins and secreted toxins that are precisely controlled in response to environmental changes. GGDEF domain protein from Staphylococcus (GdpS) is the only conserved staphylococcal GGDEF domain protein that is involved not in c-di-GMP synthesis but in the virulence regulation of S. aureus NCTC8325. Our previous study showed that the inactivation of gdpS generates an extensive change of virulence factors together with, in particular, a major Spa (protein A) surface protein. As reported, sarS is a direct positive regulator of spa. The decreased transcript levels of sarS in the gdpS mutant compared with the parental NCTC8325 strain suggest that gdpS affects spa through interaction with sarS. In this study, site mutation and complementary experiments showed that the translation product of gdpS was not involved in the regulation of transcript levels of sarS. We found that gdpS functioned through direct RNA-RNA base pairing with the 5′ untranslated region (5′UTR) of sarS mRNA and that a putative 18-nucleotide region played a significant role in the regulatory process. Furthermore, the mRNA half-life analysis of sarS in the gdpS mutant showed that gdpS positively regulates the mRNA levels of sarS by contributing to the stabilization of sarS mRNA, suggesting that gdpS mRNA may regulate spa expression in an RNA-dependent pathway.